A novel approach based on multiple fish species and water column compartments in assessing vertical microlitter distribution and composition. (1st March 2021) - Palazzo, Luca; Coppa, Stefania; Camedda, Andrea; Cocca, Mariacristina; De Falco, Francesca; Vianello, Alvise; Massaro, Giorgio; de Lucia, Giuseppe Andrea
Abstract: The assessment of the distribution and composition of microlitter in the sea is a great challenge. Biological indicators can be an irreplaceable tool since they measure microlitter levels in their environments in a way that is virtually impossible to replicate by direct physical measurements. Furthermore, trends can provide policymakers with statistically robust analysis. We looked into the capacity of multiple fish species to describe the distribution and composition of microlitter vertically across different compartments of the water column. A total of 502 individuals from six selected species ( Scomber scombrus, Oblada melanura, Spicara smaris, Boops boops, Merluccius merluccius and Mullus barbatus ) were collected on the western side of Sardinia island and allocated to three compartments: surface, mid-water and bottom. The species of the surface exhibited a higher frequency of occurrence (41.89%) of microlitter ingestion, compared to those of the mid-water and bottom (19.60%; 22.58%). A significant difference in the average number of ingested microlitter was found between the surface and the bottom compartment. All the microlitter fragments found were analysed through Fourier Transform Infrared Spectroscopy (FTIR). The comparison of the expected buoyancies of the polymers identified puth faith in the allocation of the species to the respective compartments. Therefore, considering the Marine Strategy Framework Directive objective, this approach could be useful in assessing microlitter distribution and composition vertically across the water column. Graphical abstract: Image 1 Highlights: Fish species and compartments can describe microlitters distribution and composition. Fish in the surface compartment had the highest incidence of microlitter ingestion. Average number of microlitter items was significantly different for compartments. Polymer analysis gave confidence to the allocation of fish species to compartments. Abstract : This study suggests that by using multiple fish species, allocated to compartments of the water column, we are able to assess vertical microlitter composition and distribution in marine environments.